Egg Consumption and Multi-Domain Cognitive Function in a Representative Sample of Older U.S. Adults (P14-004-19) - Bishop, Nicholas (Curr Dev Nutr, 2019)
OBJECTIVES: Existing research supports a positive relationship between egg intake and cognitive function in older populations, though the impact of whole egg consumption on multi-domain cognitive function and cognitive decline in representative samples of older adults has not been described. We examined the association between egg consumption, cognitive performance, and cognitive change in a representative sample of U.S. adults age 65 and older. METHODS: We drew observations from the 2012 and 2014 Health and Retirement Study (HRS) and the recently released 2013 Health Care and Nutrition Study (HCNS). The analytic sample contained 3835 respondents, representing a weighted population of 37,806,082 community-dwelling U.S. adults age 65 and older in 2013. Path analytic models were estimated to identify the association between egg consumption groups (none, ≤1 serving per week, 2–6 servings per week, ≥7 servings per week) and cognitive performance across domains of working memory, executive function, and global mental status. First-order autoregressive models were used to assess change in cognition over the two-year observational period. RESULTS: Though bivariate analyses suggested that moderate egg consumers had the best cognitive performance at baseline, egg consumption was not associated with cognitive performance or cognitive change when adjusting models for covariates known to have a robust association with cognitive health such as race/ethnicity, education, and physical activity. Follow-up analyses suggested that overall dietary intake was not meaningfully related to egg consumption, though intake of specific nutrients contained in eggs such as cholesterol and choline generally increased with greater egg consumption. CONCLUSIONS: These results suggest that egg consumption does not benefit, nor is detrimental to, the cognitive health of older adults. Further studies of whole egg consumption and cognitive performance would benefit from controlled experimental settings, extended follow-up periods to measure cognitive change, and assessment of both community-dwelling and institutionalized older adults. FUNDING SOURCES: This research was supported by funding from the American Egg Board/Egg Nutrition Center.